P402 Systemic steroids vs. local acting steroids: Relative risk for corticosteroid-related adverse events. (25th January 2019) - Timeus, S; Hofmann, R
Abstract: Background: The efficacy of systemic corticosteroid to treat active inflammatory bowel diseases is well known. However, these corticosteroids, due to their systemic availability are associated with potentially serious side effects. Budesonide offers an effective therapy option, being a locally acting steroid. Budesonide has a targeted delivery system for ileum/colon. Absorption is followed by rapid inactivation by the liver resulting in low systemic circulation and activity. The safety profile with respect to steroid-related adverse events favours budesonide (RR=1.64; 95% CI 1.34–2.00) (Table 1). 1 Methods: In this review, the number of adverse events (AE) reported to the Eudravigilance (covering the EU), FAERS (USA), and Vigibase (covering 110 countries worldwide) stating steroid-related AEs were collected for budesonide and methylprednisolone, prednisolone, prednisone and hydrocortisone. All AEs under the specified clinical concept were selected for the products under review. The data were used to calculate estimated measures of effect as reporting odds ratio (ROR) and 95% CI. Results: The three databases contained a total of 559130 reports for all the active ingredients which comprised of 54988 for budesonide, 108775 for methylprednisolone, 159343 for prednisolone, 202345 for prednisone and 33679 hydrocortisone. Of these a total of 48947 concerned corticosteroid AEs associated with the products under consideration. Conclusions: The data confirms the more favourable safety profile of budesonide (the most widely used locally acting steroid) in comparison to systemic steroids. However, for specific events such as cushingoid, cataract and glaucoma the calculated ROR was higher for budesonide with a low absolute number of reports. This is not predicted considering the pharmacology of budesonide. This is likely to be explained by the unexpectedness factor which may have increased the reporting rate. It is possible that reporter were much more likely to report an AE if they thought it was unusual for the product. References 1. Ford AC, Bernstein CN, Khan KJ, et al. Glucocorticosteroid therapy in inflammatory bowel disease: systematic review and meta-analysis. Am J Gastroenterol 2011;106:590–9.